Antibiotic and heavy metal resistance in enterococci from coastal marine sediment. (June 2018) - Vignaroli, Carla; Pasquaroli, Sonia; Citterio, Barbara; Di Cesare, Andrea; Mangiaterra, Gianmarco; Fattorini, Daniele; Biavasco, Francesca
Abstract: Sediment samples from three coastal sites - two beach resorts (Beach 1 and Beach 2 sites) and an area lying between an oil refinery and a river estuary (Estuarine site) - were analyzed for antibiotic- and heavy metal (HM)-resistant enterococci. A total of 123 enterococci, 36 E. faecium, 34 E. casseliflavus, 33 E. hirae, 5 E. faecalis, 3 E. durans, 3 E. gallinarum, and 9 Enterococcus spp, were recovered. Strains resistant to erythromycin, tetracycline and quinupristin/dalfopristin (Q/D) were recovered from all sites, whereas multidrug-resistant isolates were recovered only from "Beach 2" (14%) and "Estuarine" (3.7%). As regards HM resistance, the strains showed a high frequency (68%) of cadmium and/or copper resistance and uniform susceptibility to mercury. The prevalence of cadmium-resistant strains was significantly higher among erythromycin-resistant than among erythromycin-susceptible strains. A significant association between cadmium or copper resistance and Q/D resistance was also observed at "Estuarine" site. The levels of the two HMs in sediment from all sites were fairly low, ranging from 0.070 to 0.126 μg/g, for cadmium and from 1.00 to 7.64 μg/g for copper. Mercury was always undetectable. These findings are consistent with reports that low HM concentrations may contribute to co-selection of antibiotic-resistant bacterial strains, including enterococci. Graphical abstract: Image 1 Highlights: Heavy metal- and antibiotic-resistant enterococci in coastal marine sediment. MDR enterococci in sediment from a small bay in the Adriatic Sea. Copper and antibiotic resistance association in enterococci from sediment. Abstract : In this work is reported a significant association between specific antimicrobial and heavy metal resistances in enterococci from marine uncontaminated sediments.